Is it possible to use pesticides safely? - Tokhtar, K.I.; Gavrilyuk, Yu.V. (AgroChemistry and Soil Science, 2020)
The review article shows the chemical nature of the processes that occur due to the use of pesticides in agricultural production. Various negative aspects of the impact of pesticides and their residues on cultivated plants and the natural environment, in particular on the soil, are considered. Numerous references to the modern scientific literature and results of own long-term research in the field experiments are used as arguments for the purpose of carrying out ecological examination of herbicides. The results of experiments eloquently indicate the high phytotoxicity of pesticides against the cultivated plant during the cultivation of which they were used. In the variant without herbicides with two manual weeding (№2) the yield was the highest, and in the case of application of herbicides against this background, all variants showed a decrease in the yield of corn grain. The content of residues of most of the herbicides studied in the field experiment in the arable layer of the soil remained above the maximum allowable concentration even after five months from the moment of application. Studies showed that, in addition to the phytotoxicity of pesticides, there is also a hidden toxicity of their residues in the soil against crops grown after corn (oats, sunflower). The residues of pesticides a year after application led not only to a decrease in almost all variants of oat and sunflower yields, but also to the deterioration, in some cases, of the physical condition of plants. The effect of the herbicide aftereffect on yield reduction occurred even in cases where the residues did not exceed the allowable concentration. The results of the analysis of the situation leave no doubt that the current practice of using pesticides requires in-depth review, with emphasis in particular on integrated programs - in combination, primarily biological, agronomic and genetic methods and very limited use of pesticides.